P748Vascular smooth muscle cell proteome changes in a high fat diet animal model of atherogenesis. (15th July 2014) - Rocchiccioli, S; Ucciferri, N; Viglione, F; Citti, L; Parodi, O; Pelosi, G; Trivella, MG; Cecchettini, A
Abstract: Purpose: De-differentiation and phenotype changes in vascular smooth muscle cells (VSMCs) are hallmarks of vascular disorders such as atherosclerosis (ATS). High fat diet pigs were exploited as model of accelerated coronary ATS. In the present study, a gel-free proteomics approach was proposed to highlight protein markers modulated during atherogenesis and plaque growth in cultured VSMCs obtained from coronary and femoral arteries. Methods: Protein extracts from cultured VSMCs obtained from coronary and femoral arteries of pigs that had been fed with standard (CTRL) and high fat (HF) diet were digested with trypsin. Peptide mixtures were fractioned by HPLC and collected for ESI QTOF analyses. Protein expression variations amongst different cell specimens were examined and the correlation between stage of ATS development and protein modulations were immunohistologically assessed. Confocal microscopy was used to characterise cell morphology. Results: Histological analysis showed intact coronary wall in CTRL (arteries from healthy pigs), early ATS changes in femoral arteries and fibrofatty atheromas in coronary segments (cross-sectional lesion area of 0, 05-0, 1 mm2, and 0, 3- 3, 0 mm2 respectively) of HF pig. Comparing the proteomes of VSMCs isolated from healthy coronaries, pre-lesional femoral arteries and atherosclerotic coronaries allowed the highlighting, among the 264 identified proteins, of four functional protein classes. In particular, redox enzymes (i.e. catalase, superoxide dismutase, peroxiredoxin), related to energetic metabolism mitochondrial proteins (i.e. cytochrome c oxidase, succinyl trasferase), annexins (i.e. the anti-inflammatory Annexin-A1) and focal adhesion molecules (i.e. moesin, thymosin, integrin beta 1) showed differential expressions depending on the ATS stage. Conclusion: In overt atherosclerosis, VSMCs acquire a distinct protein "signature" that suggests an increase of redox events and mitochondrial damage. Focal adhesion pathways seem to have a pivotal role in the onset of VSMC pathological phenotype and this study may suggest possible targets for therapeutic treatment in proliferative disorders.